Anticancer and Free Radical Scavenging Competence of Zinc Oxide Nanoparticles Synthesized by Aqueous Leaf Extract of Phyllanthus acidus - Arunachalam Chinnathambi; Sulaiman Ali Alharbi; Deepika Joshi; Haiter Lenin (Bioinorganic Chemistry and Applications)
The purpose of this study was aimed to investigate the zinc oxide nanoparticles (ZnONPs) synthesizing efficiency of aqueous leaf extract of Phyllanthus acidus. Furthermore, the antioxidant and anticancer activities of synthesized ZnONPs were also investigated through the in-vitro approach. The obtained results show that the aqueous extract of P. acidus can synthesize ZnONPs, as evidenced by a sharp absorbance peak at 375 nm. The Fourier transform infrared spectroscopy (FTIR) analysis confirmed that the aqueous extract contained significant numbers of functional groups, which were involved in reducing zinc nitrate into ZnONPs. Also, they participate in the capping and stabilization of synthesized ZnONPs and their size ranged from 27.14–35.74 nm with a spherical shape . The results obtained in ABTS radical scavenging activity 1, 1-diphenyl-2-picryl-hydroxyl (DPPH), hydrogen peroxide (H2O2), and 2,2′-Azino-Bis(3-ethylbenzene thiazoline-6-sulfonic acid) (ABTS) assays declared has excellent in-vitro radicals scavenging activity with reasonable IC50 values. Interestingly, these green synthesized ZnONPs have an excellent anticancer activity against human epidermoid carcinoma (Hep3) cell line in an in-vitro approach. These findings imply that an aqueous leaf extract of P. acidus can be used to synthesize pharmaceutically valuable ZnONPs. To consider such nanomaterials as potential therapeutic agents, optimization and in-vivo biomedical studies are required.